Perbandingan Stomata dan Trikoma Daun Famili Araceae di Kabupaten Jember dan Pemanfaatannya sebagai Booklet - Arrizca Dwi Amaliya Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Indonesia is a diverse country with a high level of plant biodiversity, including Araceae family plant species located in Jember Regency. This plant family is known to live in any area from high to lowlands. Thus, many studies use the Araceae family as the subject. However, leaf anatomy of this plants family, precisely the stomata and trichome parts which are then associated with the altitude of the region, is rarely discussed. This study aims to know characterization of stomata and trichome of the Araceae family in several areas of Jember Regency based on the region altitude. This study also explores its utilization as an assisting booklet for learning books in educational institutions. This research is conducted by sampling the Araceae family plants using a systematic random method. The results of this study will be in the form of descriptive quantitative. Based on data from Jember Central Statistics Agency, this research only use four of the six altitude ranges such as 0-25 masl, 25-100 masl, 100-500 masl, and 500-1000 masl. Furthermore, the results of the research were developed in the form of a booklet which was first tested by selected expert observers. The research results showed a denser of stomata and trichome density in areas with an elevation of 0-25 masl compared to those at elevations of 500-1000 masl. The results that will be obtained from this study are differences in the number of stomata and trichome in the leaves of Araceae family plants selected based on the altitude of the region. Based on this feasibility test, the booklet was found to be successful and valid for further development of the research findings with minor revisions.
FINALISASI oleh Arif 2026 Mei 22
Keywords: altitude; araceae; stomata; trichome; validation